Does PET/CT render software registration obsolete? - Pietrzyk, U. (Nuklearmedizin - NuclearMedicine, 2005)
It was the success of software-based image registration that eventually led to the introduction of hardware-based concepts for image fusion, such as combined PET/CT tomographs. A prototype PET/CT was first presented in 1998, with various commercial designs to follow since 2000. PET/ CT is used primarily as a diagnostic modality in the field of extra-cerebral oncology imaging. The major advantage of combined imaging over retrospective software registration is the nearly identical position of the patient during both complementary examination, and therefore tomograms of identical parts of the body can be provided in spatially-corresponding slices. Despite the availability of hardware combinations of complementary imaging modalities software-based image registration, however, still inherits a major role in subsequent data processing, in particular when individual imaging modalities other than combined PET/CT are being used during patient workup. Furthermore, software is likely to become an important tool for the correction of residual motion-induced mis-registration within combined PET/CT data sets, and for follow-up studies involving, for example, CT, PET, and PET/CT. Therefore, flexible algorithms that utilize nonlinear interpolation schemes implemented on fast computer systems are needed, and will continue to contribute to successful image registration and fusion in clinical practice.
Keywords: PET/CT; multi-modality image registration; image fusion